2022
DOI: 10.3389/fcell.2022.828683
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RNA Modifications in Diverse Cellular Functions

Abstract: Chemical modifications of RNA molecules regulate both RNA metabolism and fate. The deposition and function of these modifications are mediated by the actions of writer, reader, and eraser proteins. At the cellular level, RNA modifications regulate several cellular processes including cell death, proliferation, senescence, differentiation, migration, metabolism, autophagy, the DNA damage response, and liquid-liquid phase separation. Emerging evidence demonstrates that RNA modifications play active roles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 216 publications
(433 reference statements)
0
30
0
Order By: Relevance
“…In the 1970s, researchers discovered the existence of m 5 C in RNA, and high-throughput detection methods found that m 5 C is an RNA modification widely present in mRNA and lncRNA, including transfer RNA (tRNA), ribosomal RNA (rRNA), Long non-coding RNA (lncRNA), small nuclear RNA (snRNA), microRNA (miRNA), and enhancer RNA (eRNA) [94]. Modifications at specific positions of m 5 C in mRNA show different regulatory activities, they can promote or inhibit translation; in tRNA, m 5 C can stabilize secondary structure and affect anticodon stem-loop conformation; in rRNA, m 5 C can affect translation preservation Authenticity [52]. The m 5 C methyltransferase usually uses S-adenosylmethionine (SAM) as the methyl donor to transfer the methyl group to the fifth carbon position of the RNA cytosine base [95].…”
Section: Cmentioning
confidence: 99%
See 3 more Smart Citations
“…In the 1970s, researchers discovered the existence of m 5 C in RNA, and high-throughput detection methods found that m 5 C is an RNA modification widely present in mRNA and lncRNA, including transfer RNA (tRNA), ribosomal RNA (rRNA), Long non-coding RNA (lncRNA), small nuclear RNA (snRNA), microRNA (miRNA), and enhancer RNA (eRNA) [94]. Modifications at specific positions of m 5 C in mRNA show different regulatory activities, they can promote or inhibit translation; in tRNA, m 5 C can stabilize secondary structure and affect anticodon stem-loop conformation; in rRNA, m 5 C can affect translation preservation Authenticity [52]. The m 5 C methyltransferase usually uses S-adenosylmethionine (SAM) as the methyl donor to transfer the methyl group to the fifth carbon position of the RNA cytosine base [95].…”
Section: Cmentioning
confidence: 99%
“…m 5 C promotes viral mRNA translation. In the study of Courtney, a highly prevalent modification of m 5 C was detected on HIV-1 gRNA in infected cells, with m 5 C levels about 14 times higher than cellular mRNA.…”
Section: The Role Of M 5 C Modification During Hiv-1 Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have revealed that m6A methylation plays a crucial role in the regulation of the degeneration process and mediates the occurrence and progression of multiple degeneration-related disorders (Li et al, 2022b;Peng et al, 2022). Intriguingly, prior studies reported that epigenetic modifications including m6A methylation played a prominent role in autophagy regulation (Tang et al, 2022;Wilkinson et al, 2022). Moreover, m6A modification has been reported to directly regulate the expression of autophagy-related (ATG) genes and modulate the cellular autophagy level, and the effects of the m6A methylation on autophagy are dependent on the disease context (Han et al, 2021).…”
mentioning
confidence: 99%